DEVELOPING THE LEARNING SET FOR THE TOPIC OF PYTHAGOREAN THEOREM USING PROBLEM SOLVING APPROACH REFERS TO THE LEARNING TRAJECTORY WITH PROBLEM SOLVING STUDENT’S ABILITY ORIENTATION - Afifah Nur Indah Sari; Ariyadi Wijaya (Jurnal Pedagogi Matematika, 2017)
This study aims to produce learning set that includes Lesson Plan and Student Worksheet for the topic of Pythagorean theorem which are valid, practical and effective. Learning set that are developed using problem solving approach refers to the learning trajectory with problem solving ability oriented to junior high school students of class VIII. Type of the research was research and development with ADDIE  model  consisting of Analysis, Design, Development, Implementation, and Evaluation. This research paradigm is mixed method research by using embedded mixed method design. The instruments used in this research were validation sheets for measuring the validity of the learning set, student’s  and  teacher’s  questionnaire  for  measuring  the  practicality,  and  test  to measure  the effectiveness of learning set. The results of this research are lesson plan and student worksheets using problem  solving  approach  refers  to  the  learning  trajectory.  Based  on  the  results  of  validation assessment, the lesson  plan was  very  valid  with a score  of  4,24  on  a  scale  5.  While  validation assessment of student worksheets obtained a score of 4,15 on a scale 5 with “valid” category. Based on practicality assessment  results of student’s questionnaire obtained a score of 3,01 on a scale 4 with “practical”  category  and  teacher’s questionnaire obtained  a  score  of  3,45  on  a  scale  4  with  “very practical” category. Effectiveness assesment using test obtained the level of completeness is 84.34%. Then,  the average  test  score  of  the  class  obtained  of  81.81  which  indicates  greater  than minimum accomplishment criteria i.e. 75. So that, the learning set is effective.Keyword: learning set, problem solving, learning trajectory